Enrico Castelli and the philosophical “diarística” (Iter, 2022)
I n the light ofa re-reading o f EnricoCastellVs work, the author gives herey along with a profile o f thephilosopher, a moved memory ofhe who was his masterand particularfeatures of his peculiar way of thinking. What stands out in a specialway is the place common sense and lived experience occupy over allkinds of traditional intellectualism; and it defines his philosophy as a“theological existencialism ”.